2005
DOI: 10.15288/jsa.2005.66.82
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative effects of acute alcohol consumption, individual differences and situational perceptions on sexual decision making.

Abstract: Objective-Past alcohol administration research has produced mixed findings regarding the role of acute alcohol consumption on sexual decision making. The purpose of this study was to evaluate a more complex theoretical model that places alcohol's acute effects in context, through the inclusion of background measures as well as affective and cognitive responses to the specific situation.Method-College students (90 men, 90 women) completed a survey that included measures of individual difference characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 42 publications
4
73
1
2
Order By: Relevance
“…colleagues (2002, 2004a,b) similarly found that acute alcohol intoxication increased men's and women's risky sex intentions during role playing of risky sexual situations. Using a written hypothetical risky sexual scenario, Abbey et al (2005) reported that alcohol consumption signifi cantly increased participants' intentions of engaging in unprotected sex in such a situation. In sum, extant experimental research using a variety of stimulus material has provided consistent evidence that alcohol consumption increases heterosexual risk-taking intentions.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
See 2 more Smart Citations
“…colleagues (2002, 2004a,b) similarly found that acute alcohol intoxication increased men's and women's risky sex intentions during role playing of risky sexual situations. Using a written hypothetical risky sexual scenario, Abbey et al (2005) reported that alcohol consumption signifi cantly increased participants' intentions of engaging in unprotected sex in such a situation. In sum, extant experimental research using a variety of stimulus material has provided consistent evidence that alcohol consumption increases heterosexual risk-taking intentions.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
“…Three separate studies have investigated the joint infl uence of being both sexually aroused and intoxicated (Abbey et al, 2005;George et al, 2009;MacDonald et al, 2000). Abbey et al (2005) found that men's and women's perceived sexual arousal predicted their risky sex intentions over and above alcohol's effects. MacDonald et al (2000) found that alcohol consumption increased sexual risk-taking intentions only for men who reported higher levels of sexual arousal.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effects of sexual arousal, many studies have measured subjective or genital sexual arousal and found that individual differences in sexual arousal in response to arousing stimuli were associated with individual differences in the self-reported readiness to engage in unprotected sex (Abbey, Saenz, & Buck, 2005;Norris et al, 2009) or differences in self-estimated likelihood to sexually aggress in men (Davis, Norris, George, Martell, & Heiman, 2006a). Measured sexual arousal has also been found to mediate the effects of alcohol on the likelihood of agreeing to unprotected sex in men and women Prause, Staley, & Finn, 2011), women's rape myth acceptance (Davis, Norris, George, Martell, & Heiman, 2006b), and men's self-rated likelihood to sexually aggress (Davis et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In general, positive alcohol outcome expectancies have been associated with more risk taking than negative beliefs about alcohol (Fromme et al, 1997). Alcohol-related sexual beliefs have been related to unsafe sexual outcomes including unprotected sex (Abbey et al, 2005;Cooper, 2002;George and Stoner, 2000). Research suggests that positive expectancies about the sexual-enhancement effects of alcohol predict more frequent substance use in sexual contexts (Kalichman et al, 1998).…”
mentioning
confidence: 99%